Studenci w świecie Internetu. Odniesienia do rodziny i związków partnerskich - Milart, Ewelina (Kultura-Społeczeństwo-Edukacja, 2022)
The article below presents the functioning of students who use the Internet in their family and partnership lives. Particular attention is paid to present developmental characteristics of youth taking into account the categories of family and partnership. The paper presents research on the functioning of adolescents in the selected categories. Own research analysis concerns showing how students use the Internet in both relationships.